FINANCIAL PERFORMANCE AND FINANCIAL DISTRESS BEFORE AND DURING THE COVID-19 PANDEMIC: Empirical Evidence from the Tourism and Hospitality Firms Listed on Indonesia Stock Exchange - Soleha, Nurhayati; Mayuni, Ani; Ismawati, Iis (PT Larva Wijaya Penerbit, 2022)
This study aims to analyze differences in financial performance and financial distress before and during the covid-19 pandemic in Indonesian tourism and hospitality companies listed on the Indonesia Stock Exchange (IDX). Financial performance is measured using the Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) proxies, whilst Financial distress is measured using the Altman Z-Score model. The tests used are descriptive statistics test, normality test by using Kolmogorov-Smirnov, and hypothesis test by using Wilcoxon Signed Rank Test from 25 firms for the 2019-2020 period. The results of this study indicate that there are differences in the conditions of financial performance and financial distress before and during the covid-19 pandemic. Most of the companies (96%) was a decline in financial performance conditions during the pandemic so many companies experienced financial difficulties.